IMPACT OF THE COVID-19 DISEASE ON THE APPLICATION OF VEHICLE ROUTING PROBLEMS IN PRACTICE - Luka Olivari; Srećko Đuranović (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
The COVID-19 pandemic has, among other things, disrupted global supply chains, through a large increase in demand for medical supplies with simultaneous movement restrictions, increased transportation costs, and reduced labour availability. For many years, transport, distribution, and logistics processes have been optimized by solving the Vehicle Routing Problem (VRP). Optimizing logistics processes is especially important during a pandemic when resources are limited, and disruptions can endanger human lives. This paper aims to investigate the impact of COVID-19 on the Vehicle Routing Problem in practice due to new limitations and challenges by reviewing the literature.